Performance evaluation and calibration of soil moisture sensors for scheduling of irrigation in brinjal crop (Solanum melongena L. var. Pusa Shyamla) - KUMAR, JITENDRA; PATEL, NEELAM; RAJPUT, THAKUR BAHADUR SINGH; KUMARI, ARTI; RAJPUT, JITENDRA (Journal of Soil and Water Conservation, 2020)
This study evaluated the performance of soil moisture sensors i.e. tensiometer, watermark and frequency domain reflectometry (FDR) under field conditions during growing season of brinjal crop. On comparing performance of different sensors (tensiometer, watermark and FDR) had a coefficient of determination (R2) range of 0.68–0.86, 0.68–0.83 and 0.79–0.85, respectively against gravimetric methods at different soil profile layers of 20 cm, 30 cm, 45 cm and 60 cm. Statistically, the performance of tensiometer was found best on comparing with watermark and FDR at 20 cm and 30 cm depth, respectively. The tensiometer had the minimum RRMSE and Md values of 10.09% and – 0.82, respectively with high R2 value of 0.86 at 30 cm soil depth. Watermark and FDR performance at 60 cm depth was found appreciable with mean difference of 0.19 and 1.35, RRMSE value 12.87, 12.52 and R2 value 0.83, 0.86,respectively. The average performance of frequency domain reflectometry and tensiometer had greater coefficient of determination (R2) than watermark sensor at different depths by comparing their readings with that obtained by gravimetric method in brinjal crop. The watermark showed a consistent and increasingly drier estimate of water content compared to tensiometer.